The Efficiency of Using Ozone Gas and Heat to Control Larvae and Adult Stage of Red Flour Beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) - Baghdad Science Journal (مجلة بغداد للعلوم, 2017)
The effect of ozone gas with temperatures 35. 40 and 45 Celsius to control on larval and adult stages of Tribolium castaneum was tested and at time of exposure 1.0, 3.0, 7.0, 9.0, 11.0, 13.0 hours and the level of relative humidity prevailing during the test 45 ± 1%. Results showed significant differences between the exposure times, when the percentage of mortality 100% between larvae (primary, intermediate and advanced) in the treatment effect at a temperature of 35 Celsius with ozone gas at exposure time to 9.0, 11.0, 11.0 hours for the three ages respectively, and adult (male and female) in the same treatment when the three heat degrees had given ratios the total mortality reached 100% of both males at exposure time to 7.0 ,3.0, 1.0 hour respectively and females at exposure time 9.0 ,7.0 ,1.0 hour respectively, While completely failed under the effect of a heat treatment at temperatures of 35 Celsius for both stages respectively, while the effect was clear when the temperature is 45 Celsius where the of total mortality of 100% when the heat treatment of the stage of the larval and adult at the time 7.0, 3.1, 1.0 hour respectively. This means that the combined effect of ozone gas with temperatures has resulted in the reduction of the time needed to get the total mortality in both insect stages and significantly influential and that mortality rates in the two stages were increasingly higher degree of exposure used heat and high heat was the lead in reducing the time of exposure and even access to the total mortality.